High-strength hot-dip galvanized steel, preparation method and application thereof in manufacturing fasteners
By using low-carbon boron steel in hot-dip galvanized steel, optimizing quenching and pretreatment processes, introducing transition layers and galvanized layers, and using Fe, Ni, and Al elements, the problem of insufficient interface bonding strength and corrosion resistance is solved. It realizes high-performance hot-dip galvanized steel preparation, improving the comprehensive performance and service life of fasteners.
Patent Information
- Application Number
- CN202411444426.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing hot-dip galvanized steel has shortcomings in interface combination strength, fastener strength and corrosion resistance, resulting in insufficient plating peeling, cracking and corrosion resistance, limiting its application range and service life.
Low-carbon boron steel is used as the base material, and a micro-decarbonized layer is formed through step-up temperature quenching, the pre-treatment process and hot-dip galvanizing process are optimized, the transition layer and galvanized layer are introduced, and the coating performance is improved by using Fe, Ni, and Al elements. Improve interface bonding strength and corrosion resistance through lattice matching interface and composite reinforcement structure.
It significantly improves the interface combination strength between the plating and the substrate, the strength of the fastener and the corrosion resistance of the plating, reduces production costs, simplifies the process flow, realizes energy-saving and environmentally friendly effects, and extends the service life of the fastener .
Smart Images

Figure CN118957476B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of galvanized steel materials, and in particular to a high-strength hot-dip galvanized steel, a preparation method and application thereof in manufacturing fasteners. Background Art
[0002] In modern industry and infrastructure construction, high-strength hot-dip galvanized fasteners play a vital role. They are widely used in photovoltaic power generation, 5G communications, ultra-high voltage transmission lines, high-speed guardrails and other fields, and undertake the connection and fixing functions of key components. These application scenarios put forward strict performance requirements on fasteners, including high strength, excellent interface bonding strength and excellent corrosion resistance. High strength is a basic performance that fasteners must have, which determines whether fasteners can provide reliable connections under complex stress conditions.
[0003] Taking photovoltaic power generation and ultra-high voltage power transmission as examples, fasteners need to withstand static and dynamic composite stresses such as wind loads and ice loads for a long time, and the loads change frequently. Improving strength performance is crucial to ensure the safety of key components. In applications such as high-speed guardrails, fasteners must also have sufficient toughness to avoid brittle failure. Interface bonding strength is a key indicator to measure the bonding quality between the coating and the substrate of hot-dip galvanized fasteners. Excellent bonding strength is a prerequisite for the coating to play a corrosion-resistant role. It not only affects the service life of the fasteners, but also affects the reliability and safety of the entire structure. Taking 5G communication base stations as an example, their fasteners are directly exposed to the atmospheric environment. Good bonding strength can prevent the coating from falling off, cracking and other failures under wind and sun, thereby maximizing its service life and reducing maintenance and replacement costs. Corrosion resistance is the core advantage of hot-dip galvanized fasteners, and it plays an indispensable role in extending the life of fasteners and ensuring the safety of connection structures.
[0004] As we all know, steel materials are very susceptible to electrochemical corrosion, and the volume expansion of their corrosion products can also lead to stress corrosion cracking. The hot-dip galvanizing process forms a dense zinc coating and zinc-iron alloy layer on the surface of the fasteners, and utilizes the cathodic protection and isolation effects of the coating to significantly improve the corrosion resistance of the fasteners. Taking offshore wind power fasteners as an example, their service environment is harsh and the salt spray concentration is high. Continuously improving the corrosion resistance of the coating is crucial to ensure the safe operation of wind turbines and extend their service life.
[0005] In summary, high strength, excellent interface bonding strength and outstanding corrosion resistance are the key performance requirements that hot-dip galvanized high-strength fasteners must meet. The continuous improvement of these properties can not only significantly improve the overall performance of the fasteners themselves, but also expand their application range, improve the safety, reliability and service life of downstream products, and provide important support for the accelerated development of new energy, new infrastructure and other fields. Therefore, focusing on the above performance requirements, continuously innovating the materials and processes of hot-dip galvanized high-strength fasteners is of great significance to promoting technological progress in the industry and assisting the construction of major national projects.
[0006] However, hot-dip galvanized steel currently has deficiencies in terms of interface bonding strength, fastener strength and corrosion resistance: First, in terms of interface bonding strength, hot-dip galvanized fasteners produced by traditional processes often have problems with insufficient bonding strength between the coating and the substrate. This is mainly due to the fact that the pre-treatment of the fasteners before hot-dip galvanizing is not perfect, and there are oxides and impurities on the surface of the substrate, which affect the effective wetting and metallurgical bonding between the zinc liquid and the steel base. At the same time, the brittle and hard blocky ζ phase generated during the galvanizing process also weakens the bonding strength of the interface. Insufficient bonding strength can easily lead to peeling and cracking of the coating during use, lose its protective effect, and accelerate the corrosion failure of the fasteners. Secondly, in terms of fastener strength, both of the current mainstream production processes have certain limitations. Although the use of non-quenched and tempered steel can obtain higher strength through cold hardening, the alloy composition is complex and the smelting cost is high, resulting in expensive raw materials, high processing hardness, and high production costs. Although the cost of raw materials in the traditional quenched and tempered steel process is relatively low, the heat treatment energy consumption of quenching and high-temperature tempering is very large. The power consumption per ton of product is close to 600kW·h, and the production cost is also high. In addition, the quenched martensitic structure has high hardness and poor toughness. If the tempering is not timely, it is easy to cause deformation and cracking, affecting the performance of the fasteners. Furthermore, in terms of corrosion resistance, although hot-dip galvanizing can significantly improve the corrosion resistance of steel fasteners, in some harsh environments, such as marine atmosphere, tidal splash zone and other high salt fog and high humidity environments, the corrosion resistance of the galvanized layer is still insufficient. Long-term exposure to hot and humid, chlorine-containing environments, the coating is prone to "white rust", zinc oxides and hydroxides are generated in large quantities, and the protective effect of the coating is quickly lost. In some industrial atmospheric environments, the erosion of acid rain and sulfur-containing pollutants will also accelerate the dissolution and destruction of the coating. The lack of corrosion resistance of the coating limits the scope of use and life of hot-dip galvanized fasteners.
[0007] In view of the above shortcomings, it is urgent to develop a new hot-dip galvanized steel process. By optimizing the material composition of fasteners, improving the heat treatment system, innovating the surface treatment process, etc., while reducing production costs, the interface bonding strength between the coating and the substrate, the toughness of the fasteners, and the corrosion resistance of the coating can be improved from a mechanism perspective to meet increasingly stringent application requirements. Summary of the invention
[0008] (1) Technical issues solved
[0009] The purpose of the present invention is to provide a high-strength hot-dip galvanized steel, a preparation method and its application in manufacturing fasteners, so as to solve the problems of insufficient interface bonding strength, toughness of fasteners and corrosion resistance of the coating of the current hot-dip galvanized steel.
[0010] (2) Technical solution
[0011] In order to achieve the above object, the present invention provides the following technical solutions:
[0012] A method for preparing high-strength hot-dip galvanized steel comprises the following steps:
[0013] S1: Cleaning carbon steel parts;
[0014] S2: performing stepwise heating on the carbon steel part obtained in step S1, and then performing quenching treatment to obtain a quenched carbon steel part;
[0015] S3: pickling and water washing the quenched carbon steel part obtained in step S2 in sequence, and performing a plating-assisting treatment using a plating-assisting solution;
[0016] S4: immersing the carbon steel part obtained by the process in step S3 into a molten zinc solution for hot-dip galvanizing, and then sequentially performing centrifugal dezincification, water cooling, and discharging treatment to obtain the high-strength hot-dip galvanized steel.
[0017] Preferably, the composition of the carbon steel part is: C: 0.20-0.27%, B: 0.001-0.003%, Si: 0.02-0.06%, P: ≦0.020%, Cr: 0.10-0.20%, and the rest is Fe.
[0018] The carbon steel parts of the present invention are low-carbon boron steel, and this composition design can significantly improve the strength and toughness of the steel. The appropriate amount of carbon content ensures the strength of the steel, and the addition of trace boron can refine the grains and improve the plasticity and toughness of the steel. At the same time, the addition of silicon and chromium can improve the hardenability and wear resistance of the steel, and further enhance the comprehensive mechanical properties of the hot-dip galvanized steel.
[0019] Preferably, in step S2, the carbon steel part obtained in step S1 is subjected to stepwise heating to slightly decarburize the surface of the carbon steel part;
[0020] The process parameters of the step-by-step heating are: first, the temperature is raised from room temperature to 340-350°C at a rate of 1-5°C / min, then to 550-560°C at a rate of 1-3°C / min, and then to the quenching temperature at a rate of 0.5-1.5°C / min. The quenching temperature is 720-850°C. The heating atmosphere of the step-by-step heating is a mixed atmosphere of nitrogen and methanol; the carbon potential of the heating atmosphere is 0.08%-0.12%. The methanol gas is generated by directly dripping liquid methanol into the heating area.
[0021] Preferably, in step S2, the quenching liquid used in the quenching is a 2% by mass polyethylene glycol aqueous solution, and the temperature of the quenching liquid is 35-40°C;
[0022] The hardness of the quenched carbon steel part is greater than 40HRC, and the thickness of the surface micro-decarburization layer is 0.03-0.08mm.
[0023] Step S2 of the present invention cleverly balances the strength, hardness and corrosion resistance of carbon steel parts through a quenching process. A step-by-step heating process is adopted to accurately control the heating rate and the carbon potential of the protective atmosphere to form a micro-decarburized layer on the surface of the carbon steel. Although this low-carbon area slightly reduces the surface hardness, it significantly improves the toughness and crack resistance of the parts, and at the same time improves the corrosion resistance after hot-dip galvanizing. This innovative method provides an effective way to obtain high-performance hot-dip galvanized steel parts, and successfully balances the two key performance indicators of strength and corrosion resistance. The quenching treatment of the present invention cleverly combines the advantages of the micro-decarburized layer and the martensitic structure to achieve an optimized balance of performance. The micro-decarburized layer alleviates the stress concentration during the hot-dip galvanizing process and improves the quality and corrosion resistance of the coating. The quenching treatment forms a high-strength and high-hardness martensitic structure, which makes the hardness of the parts exceed 40HRC and greatly improves the load-bearing capacity. The selection of quenching liquid (2% polyalkylene glycol aqueous solution) and the optimization of process parameters (35~40℃) ensure uniform martensitic structure and consistent hardness distribution. The thickness of the micro-decarburized layer is precisely controlled at 0.03~0.08mm, which provides appropriate toughness and crack resistance while ensuring surface hardness, effectively balancing strength and corrosion resistance.
[0024] Preferably, in step S3, the quenched carbon steel part obtained in step S2 is sequentially subjected to pickling, water washing, and plating treatment within 1 hour after discharge;
[0025] The pickling is carried out by using a pickling agent, and the pickling time is 4 to 6 minutes; the preparation method of the pickling agent comprises the following steps: adding ferrous chloride to hydrochloric acid with a mass fraction of 5 to 6%, stirring and mixing to obtain the pickling agent; the concentration of ferrous chloride in the pickling agent is 50 to 100 g / L;
[0026] The plating-assisting solution is an aqueous solution containing 200-250 g / L ammonium chloride and 5-10 g / L zinc chloride, and the pH value of the plating-assisting solution is adjusted to 4-5 by hydrochloric acid; that is, the preparation method of the plating-assisting solution comprises the following steps: adding ammonium chloride and zinc chloride to water, stirring and mixing, and adjusting the pH value of the solution to 4-5 by hydrochloric acid to obtain the plating-assisting solution, wherein the content of ammonium chloride is 200-250 g / L, and the content of zinc chloride is 5-10 g / L;
[0027] The temperature of the plating assist treatment is 30-40° C. and the time is 30-90 seconds.
[0028] Step S3 of the present invention optimizes the pre-treatment process of hot-dip galvanized carbon steel parts, including three key steps of pickling, water washing and plating aid, aiming to obtain high-quality galvanized layer, improve corrosion resistance and ensure overall strength. Pickling uses hydrochloric acid solution and ferrous chloride accelerator to remove surface oxide layer and impurities, creating good conditions for galvanizing. Water washing removes residual acid and impurities to prevent contamination of the plating aid solution. Plating aid treatment uses ammonium chloride and zinc chloride to form a zinc-philic chloride layer to improve the wettability and bonding strength of zinc liquid and steel base. By finely controlling various process parameters, such as pickling efficiency, plating aid solution concentration, pH value, temperature and time, high bonding strength, density and uniformity of the galvanized layer are achieved. This optimized design significantly improves corrosion resistance while ensuring the strength of the parts, which is of great significance for obtaining hot-dip galvanized carbon steel parts with excellent comprehensive performance.
[0029] Preferably, in step S4, the composition of the molten zinc solution is: Fe: 0.2-0.35%, Ni: 0.030-0.045%, Al: 0.015-0.025%, and the rest is Zn;
[0030] The temperature of the hot-dip galvanizing is 520-540° C., and the time is 25-35 seconds.
[0031] Preferably, in step S5, the rotation speed of centrifugal dezincification is 550-650 rpm; and the water cooling temperature is 60-80°C.
[0032] Step S4 of the present invention optimizes the hot-dip galvanizing process, aiming to obtain a galvanized layer with excellent performance, and improve the strength, interface bonding and corrosion resistance of the coating. By optimizing the composition of the molten zinc solution (adding Fe, Ni, and Al elements), controlling the galvanizing process parameters (galvanizing temperature of 520~540℃, galvanizing time of 25~35s), and adopting centrifugal dezincification and water cooling and other coordinated regulation, the optimization of organization and performance is achieved. The Fe element improves the hardness and wear resistance, the Ni element refines the organization and improves the toughness, and the Al element forms a barrier layer to improve the interface bonding. Centrifugal dezincification ensures uniform surface quality and thickness, and water cooling inhibits the formation of brittle phases and improves toughness. The combined effect of these optimization measures significantly improves the strength characteristics, interface bonding performance and corrosion resistance of the galvanized layer, and provides important guidance for obtaining high-performance hot-dip galvanized carbon steel parts.
[0033] In general, the innovative high-strength hot-dip galvanized steel preparation method of the present invention is based on improved low-carbon boron steel. By optimizing the heat treatment process, the heat of the hot-dip galvanizing process is cleverly used to achieve the tempering effect and the formation of the galvanized layer. This process innovation of "using zinc instead of fire" eliminates the traditional separate tempering process, and effectively solves the problems of easy cracking due to quenching without tempering, and abnormal growth of the galvanized layer caused by quenched martensite. At the same time, this method greatly simplifies the preparation process, saving 110 to 130 degrees of electricity per ton of fasteners, and controlling the consumption of new water within 200 kg, reflecting significant energy-saving, cost-reduction and environmental protection benefits. This process innovation stems from a deep understanding and clever combination of the quenching and tempering mechanism and the hot-dip galvanizing mechanism. It not only ensures the high strength and coating quality of the product, but also provides a new idea for the green and efficient preparation of hot-dip galvanized steel, which has important implications for promoting the high-quality development of the manufacturing industry.
[0034] The present invention also discloses a high-strength hot-dip galvanized steel, wherein the high-strength hot-dip galvanized steel is prepared by the above-mentioned preparation method;
[0035] The high-strength hot-dip galvanized steel comprises a carbon steel layer, a transition layer and a galvanized layer on the carbon steel layer, wherein the transition layer is located between the carbon steel layer and the galvanized layer, the thickness of the transition layer is 20-60 μm, and the thickness of the galvanized layer is 40-80 μm.
[0036] In this hot-dip galvanized steel solution, the thickness of the transition layer is controlled at 20~60μm, the carbon steel layer uses low-carbon boron steel, and the thickness of the galvanized layer is 40~80μm. These designs have a significant impact on the interface bonding strength of the material, the toughness of the fasteners, and the corrosion resistance of the coating. First, the thickness of the transition layer is in the range of 20~60μm, which can ensure good bonding strength while avoiding the brittleness problem caused by the excessive thickness of the transition layer. The moderate thickness of the transition layer is conducive to the formation of a stable and continuous interface, providing sufficient bonding area, while reducing the influence of thermal stress and residual stress, and reducing the risk of interface cracking. Secondly, the thickness of the galvanized layer is controlled at 40~80μm, which can provide sufficient corrosion protection and extend the service life of the fastener. The thicker galvanized layer can act as a sacrificial anode and be corroded first, thereby protecting the internal steel matrix. At the same time, the thicker galvanized layer also means a longer corrosion path, which delays the penetration of the corrosive medium into the steel matrix. It should be noted that the thickness of the galvanized layer should not be too large, so as not to affect the assembly accuracy and appearance quality of the fastener. In summary, the hot-dip galvanized steel solution has achieved a balance in terms of interface bonding strength, fastener toughness and coating corrosion resistance by rationally designing the thickness of the transition layer, selecting low-carbon boron steel as the carbon steel layer and controlling the thickness of the galvanized layer, and can meet the application requirements of high-performance fasteners. The optimization of the transition layer thickness ensures the stability of the interface, the use of low-carbon boron steel improves the strength and toughness of the fastener, and the appropriate thickness of the galvanized layer provides reliable corrosion protection. This comprehensive performance improvement has laid the foundation for the application of hot-dip galvanized steel in the field of high-end fasteners.
[0037] Preferably, the transition layer contains ζ-FeZn 13 ,δ-FeZn 10 and Fe2B.
[0038] The strong metallurgical bonding between the transition layer and the carbon steel layer is the basis for ensuring the overall performance of hot-dip galvanized steel. The presence and composition of the transition layer also contribute to improving the strength of galvanized steel. 13 and δ-FeZn 10 It is a Fe-Zn intermetallic compound. Its hardness and strength are higher than that of pure zinc coating. The presence of these hard phases in the transition layer improves the bearing capacity of the coating. At the same time, the hard Fe2B particles are dispersed in the ζ-FeZn 13 and δ-FeZn 10 In the matrix, it plays a role of second phase strengthening, similar to hard particle reinforced composite materials. Fe2B particles hinder dislocation movement, improve the yield strength and plastic deformation resistance of the transition layer. The overall high strength characteristics of the transition layer are transferred to the carbon steel matrix through metallurgical bonding, ultimately achieving an increase in the strength of hot-dip galvanized steel.
[0039] In addition, the ζ-FeZn in the transition layer 13and δ-FeZn 10 Although they have high hardness, they still maintain good electrochemical activity and can form effective sacrificial anode protection with the pure zinc coating on the surface. The potential difference between the transition layer and the surface zinc coating causes corrosion to occur preferentially on the surface, thus protecting the carbon steel matrix. Fe2B exists in the transition layer in the form of inert particles. It does not participate in the electrochemical reaction, but can fill in the ζ-FeZn 13 and δ-FeZn 10 The transition layer forms a three-layer protective structure of "galvanized layer-transition layer-carbon steel layer", which greatly improves the corrosion resistance life of hot-dip galvanized steel.
[0040] In summary, the hot-dip galvanized steel of the present invention introduces a zeta-FeZn 13 ,δ-FeZn 10 and Fe2B transition layer. ζ-FeZn 13 ,δ-FeZn 10 The presence of Fe2B and its composite strengthening effect give the transition layer and the entire galvanized steel high strength characteristics. In addition, the transition layer, the surface galvanized layer and the carbon steel matrix form a three-layer protection. 13 and δ-FeZn 10 Providing sacrificial anode protection, Fe2B blocking corrosion channels, and jointly improving the corrosion resistance of hot-dip galvanized steel. The present invention constructs a "bridge" with high bonding force, high strength and high corrosion resistance between the galvanized layer and the carbon steel substrate through the optimized design of the transition layer components and structure, and finally obtains a new type of hot-dip galvanized steel with excellent comprehensive performance.
[0041] Preferably, the transition layer contains ζ-FeZn 13 Form a lattice matching interface with Fe2B.
[0042] The ζ-FeZn in the transition layer of the present invention 13 It forms a lattice matching interface with Fe2B. This special interface structure is conducive to significantly improving the metallurgical bonding between the coating and the steel base. The lattice matching interface refers to the interface with consistent lattice orientation and good structural matching between the two phases. This interface has high bonding strength and can effectively inhibit interface cracking and coating peeling. ζ-FeZn 13 The lattice matching interface with Fe2B means that their atomic arrangement at the interface is more coordinated and the interface bonding is tighter. Compared with the general non-lattice matching interface, the lattice matching interface greatly reduces the interface energy and reduces the interface defects, thus obtaining extraordinary interface bonding performance. 13 It forms a lattice matching interface with Fe2B, significantly improving the interface bonding strength and effectively solving the problem of coating peeling.
[0043] Preferably, the Fe2B columnar crystals in the transition layer present a tooth-like structure and are perpendicular to the transition layer interface; the average spacing of the Fe2B columnar crystals is 2-4 μm;
[0044] The ζ-FeZn in the transition layer 13 and δ-FeZn 10 Evenly distributed between Fe2B columnar crystals.
[0045] In the present invention, the Fe2B columnar crystals in the transition layer present a tooth-like structure, which is perpendicular to the transition layer interface, and the average spacing is between 2 and 4 μm, while the ζ-FeZn 13 ,δ-FeZn 10 Evenly distributed between Fe2B columnar crystals. This structure can improve material performance through the following mechanisms: First, Fe2B columnar crystals grow vertically to the transition layer interface to form a tooth-like structure, which can significantly increase the mechanical locking effect between the galvanized layer and the steel matrix and improve the interface bonding strength. The tooth-like structure increases the interface area and provides more bonding sites. At the same time, the vertically grown columnar crystals can effectively resist shear stress and prevent interface shedding. Secondly, the ζ-FeZn13 and δ-FeZn 10 Evenly distributed between Fe2B columnar crystals, forming a composite structure. These intermetallic compounds have high hardness and strength, which can enhance the mechanical properties of the transition layer. At the same time, the composite structure formed by them and Fe2B columnar crystals can effectively hinder crack propagation and improve the strength and toughness of fasteners. 13 ,δ-FeZn 10 The presence of compounds such as can improve the corrosion resistance of the transition layer and delay the penetration of corrosive media into the steel matrix. Finally, by controlling the average spacing of Fe2B columnar crystals in the range of 2~4μm, it is possible to avoid the brittleness problem caused by too dense columnar crystals while ensuring good interface bonding and mechanical properties. 13 ,δ-FeZn 10 Evenly distributed between Fe2B columnar crystals, it can improve the interface bonding strength of hot-dip galvanized steel, the toughness of fasteners and the corrosion resistance of the coating by improving the density of the transition layer, forming a composite structure, hindering crack propagation, reducing stress concentration, and improving corrosion resistance. This design takes advantage of the advantages of different phases and achieves good comprehensive performance through uniform distribution and compounding. Of course, in practical applications, it is also necessary to control the content and distribution of each phase through process optimization and composition regulation to obtain the best performance combination.
[0046] Preferably, the α-Fe in the carbon steel layer and the Fe2B phase in the transition layer form a lattice matching interface.
[0047] In this hot-dip galvanized steel solution, the α-Fe in the carbon steel layer forms a lattice matching interface with the Fe2B phase in the transition layer. This unique interface structure has an important influence on the interface bonding strength of the material, the toughness and toughness of the fastener, and the corrosion resistance of the coating. The lattice matching interface refers to the continuity of the lattice arrangement between the two phases, the matching of the lattice parameters, the close and continuous arrangement of atoms at the interface, and no obvious interface deviation or defects. The lattice matching interface formed by the α-Fe and Fe2B phases means that there is good structural matching and chemical compatibility between them, and the interface has a lower energy state and higher stability. This lattice matching interface can significantly improve the interface bonding strength, reduce stress concentration, and inhibit the initiation and expansion of microcracks. The close and continuous atomic arrangement is conducive to the smooth transfer of loads at the interface, reducing the risk of interface slip and shedding. At the same time, the formation of the lattice matching interface reduces the residual stress and thermal stress at the interface, improves the thermal stability of the interface, and reduces the interface damage caused by temperature changes during use. In addition, the lattice matching interface formed by the α-Fe and Fe2B phases can also improve the toughness and toughness of the fastener. Fe2B is a high-hardness, high-strength ceramic phase, while α-Fe has good plasticity and toughness. The two phases form a lattice matching interface, which means that there is a good match in mechanical properties between them, and an effective combination of hardness and toughness can be achieved. The Fe2B phase can hinder dislocation movement and improve the strength of the material, while α-Fe can absorb energy through plastic deformation and improve the toughness of the material. The lattice matching interface between the two phases can achieve uniform load transfer, avoid stress concentration, and reduce the initiation and expansion of cracks at the interface, thereby improving the fracture toughness and fatigue performance of the fastener. Finally, the lattice matching interface formed by α-Fe and Fe2B phases also has a positive effect on the corrosion resistance of the coating. The lattice matching interface means that the atoms at the interface are closely arranged, without obvious defects or gaps, which can effectively prevent the penetration and diffusion of corrosive media at the interface. The tight interface structure reduces the corrosion path and delays the occurrence and development of corrosion. At the same time, the Fe2B phase itself has high chemical stability and corrosion resistance, which can act as a barrier layer to prevent the penetration of corrosive media into the steel matrix and further improve the corrosion resistance of the coating. In summary, in this hot-dip galvanized steel solution, the α-Fe in the carbon steel layer and the Fe2B phase in the transition layer form a lattice matching interface, which optimizes the comprehensive performance of the material by improving the interface bonding strength, improving the toughness of the fasteners, and enhancing the corrosion resistance of the coating. The existence of the lattice matching interface ensures the stability and continuity of the interface, promotes the uniformity of load transfer and stress distribution, and hinders the penetration of corrosive media, providing important support for the development of high-performance hot-dip galvanized steel fasteners.
[0048] The present invention also provides an application of high-strength hot-dip galvanized steel, which is applied to grade 8 to grade 10 nut hot-dip galvanized layer fasteners.
[0049] Beneficial effects:
[0050] 1. The preparation method of high-strength hot-dip galvanized steel of the present invention achieves a balance between interface bonding strength, toughness and corrosion resistance of fasteners by optimizing the thickness of the transition layer (20-60 μm), selecting low-carbon boron steel as the substrate, and controlling the thickness of the galvanized layer (40-80 μm). The preparation process includes step-by-step temperature rise to form a micro-decarburization layer (0.03-0.08 mm), quenching treatment, finely controlled pre-treatment process, hot-dip galvanizing (520-540 ° C, 25-35 s) with the addition of Fe, Ni, and Al elements, and centrifugal dezincification and water cooling process. The galvanizing temperature is innovatively used to replace the separate tempering process, which simplifies the process, saves 110-130 degrees of electricity per ton of fasteners, and controls the consumption of new water within 200 kg. This method solves the problems in the traditional process, significantly improves the comprehensive performance of the parts, and achieves the effects of energy saving, cost reduction, and environmental protection, providing a new idea for the green and efficient preparation of hot-dip galvanized steel.
[0051] 2. The hot-dip galvanized steel of the present invention introduces a zeta-FeZn-containing 13 ,δ-FeZn 10 and Fe2B transition layer, and through ζ-FeZn 13 It forms a lattice matching interface with Fe2B to improve the interface bonding strength and solve the problem of coating peeling; at the same time, the composite strengthening effect of the three compounds is used to improve the overall strength; and a three-layer protective structure is formed, in which ζ-FeZn13 and δ-FeZn 10 Providing sacrificial anode protection, Fe2B blocks the corrosion channel, and together enhances the corrosion resistance. The present invention constructs a "bridge" with high bonding strength, high strength and high corrosion resistance between the galvanized layer and the carbon steel substrate, and finally obtains a new type of hot-dip galvanized steel with excellent comprehensive performance.
[0052] 3. The transition layer of the present invention comprises Fe2B tooth-shaped columnar crystals with an average spacing of 2 to 4 μm and ζ-FeZn uniformly distributed therein. 13 and δ-FeZn 10 The composite structure can increase the bonding strength by increasing the interface bonding area, while enhancing the mechanical properties of the transition layer, hindering crack propagation, and improving the toughness of the fastener. The presence of intermetallic compounds also improves corrosion resistance and delays the penetration of corrosive media. Reasonable control of the average spacing of Fe2B columnar crystals not only ensures good interface bonding and mechanical properties, but also avoids the brittleness problem caused by overcrowding. The present invention comprehensively improves the interface bonding strength of hot-dip galvanized steel, the toughness of fasteners, and the corrosion resistance of the coating.
[0053] 4. In the present invention, the α-Fe of the carbon steel layer and the Fe2B of the transition layer form a coherent interface lattice match, realizing a defect-free interface with continuous lattice arrangement and tight atomic arrangement. This structure significantly improves the interface bonding strength, reduces stress concentration, inhibits the initiation of microcracks, reduces interface residual stress and thermal stress, and improves the thermal stability of the interface. At the same time, the combination of α-Fe and Fe2B realizes an effective combination of hardness and toughness, and improves the fracture toughness and fatigue performance of the fastener. In addition, the tight coherent interface structure and the high corrosion resistance of Fe2B jointly prevent the penetration and diffusion of corrosive media, and improve the corrosion resistance of the coating. The present invention achieves comprehensive optimization of material properties from multiple aspects such as interface bonding, mechanical properties and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 This is the XRD phase analysis of the hot-dip galvanized steel prepared in Example 1 of the present invention.
[0055] Figure 2 This is a transmission electron microscope photograph of the interface between α-Fe and Fe2B in the hot-dip galvanized steel prepared in Example 1 of the present invention.
[0056] Figure 3 Fe2B and ζ-FeZn in the hot-dip galvanized steel prepared in Example 1 of the present invention 13 Transmission electron microscopy photograph of the interface.
[0057] Figure 4 This is the microstructural morphology of the hot-dip galvanized steel prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0058] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0059] Embodiment 1:
[0060] A method for preparing high-strength hot-dip galvanized steel comprises the following steps:
[0061] S1: Low carbon boron steel is reformed and formed into carbon steel parts; the composition of low carbon boron steel is: C: 0.20%, B: 0.001%; Si: 0.02%, P: ≦0.020%, Cr: 0.10%, and the rest is Fe.
[0062] S2: Use 5% by mass hydrochloric acid to pickle and remove rust on the surface of the carbon steel parts, then use 50% by mass acetone and water mixture to remove stains on the surface of the carbon steel parts, and then dry.
[0063] S3: The carbon steel parts cleaned in step S2 are subjected to step heating in sequence to achieve micro-decarburization on the surface of the carbon steel parts. After the step heating is completed, quenching treatment is immediately carried out. After the quenching is completed, the parts are tested. After the test is qualified, the quenched carbon steel parts are obtained. The process parameters of the step heating are: from room temperature to 340°C at a rate of 1°C / min, then to 550°C at a rate of 1°C / min, and then to the quenching temperature at a rate of 0.5°C / min. The quenching temperature is 720°C. The heating atmosphere for the step heating is a mixed atmosphere of nitrogen and methanol. The carbon potential of the heating atmosphere is 0.08%. The quenching liquid used during quenching is a polyalkylene glycol aqueous solution with a mass fraction of 2%, and the temperature of the quenching liquid is 35°C. The hardness of the quenched carbon steel parts is greater than 40HRC, and the thickness of the surface micro-decarburization layer is 0.03mm.
[0064] S4: The quenched carbon steel part obtained in step S3 is successively pickled and washed with water within 1 hour after being discharged, and a plating-assisting solution is used for plating-assisting treatment;
[0065] The pickling is carried out by using a pickling agent, and the pickling time is 4 minutes; the preparation method of the pickling agent comprises the following steps: adding ferrous chloride to hydrochloric acid with a mass fraction of 5%, stirring and mixing to obtain the pickling agent; the concentration of ferrous chloride in the pickling agent is 50g / L;
[0066] The auxiliary plating solution is an aqueous solution containing 200 g / L ammonium chloride and 5 g / L zinc chloride. The pH value of the auxiliary plating solution is adjusted to 4 with hydrochloric acid. The temperature of the auxiliary plating treatment is 30°C and the time is 30s.
[0067] S5: Immerse the carbon steel part obtained by the process in step S4 into a molten zinc solution for hot-dip galvanizing, and then sequentially perform centrifugal dezincification, water cooling, and discharging processes to obtain high-strength hot-dip galvanized steel.
[0068] The composition of the molten zinc solution is: Fe: 0.2%, Ni: 0.030%, Al: 0.015%, and the rest is Zn. The temperature of hot-dip galvanizing is 520℃, and the time of hot-dip galvanizing is 25s. The speed of centrifugal dezincification is 550rpm; the water cooling temperature is 60℃.
[0069] The high-strength hot-dip galvanized steel in this embodiment includes a carbon steel layer, a transition layer and a galvanized layer located on the carbon steel layer, wherein the transition layer is located between the carbon steel layer and the galvanized layer; the thickness of the galvanized layer is 40 μm, and the thickness of the transition layer is 20 μm. The transition layer contains ζ-FeZn 13 ,δ-FeZn 10 and Fe2B; ζ-FeZn in the transition layer 13 The Fe2B columnar crystals in the transition layer have a serrated structure and are perpendicular to the transition layer interface. The average spacing of the Fe2B columnar crystals is 2 μm.13 and δ-FeZn 10 Evenly distributed between the Fe2B columnar crystals; the α-Fe in the carbon steel layer and the Fe2B phase in the transition layer form a lattice matching interface.
[0070] The hot-dip galvanized steel prepared in Example 1 of the present invention was comprehensively characterized by a variety of analytical methods. XRD phase analysis results ( Figure 1 ) clearly shows the multilayer structure of the material, confirming that the transition layer is composed of ζ-FeZn 13 ,δ-FeZn 10 The carbon steel layer is composed of a mixture of Fe and Fe2B, the carbon steel layer contains α-Fe and Fe3C phases, and the galvanized layer is mainly composed of η-Zn phase. Further microstructural analysis was achieved by transmission electron microscopy. Figure 2 and Figure 3 α-Fe and Fe2B and Fe2B and ζ-FeZn are shown respectively 13 The interfaces between them all show lattice matching characteristics, indicating that the interlayers are tightly bonded, which is beneficial to improving the overall performance of the material. Figure 4 ) revealed the layered structure of hot-dip galvanized steel, which is composed of a galvanized layer, a transition layer, and a carbon steel layer from the outside to the inside. It is particularly noteworthy that the Fe2B phase in the transition layer presents a unique columnar crystal morphology. These crystals have a tooth-like structure and grow perpendicular to the transition layer interface. This special microstructure may have a positive effect on the mechanical properties and corrosion resistance of the material. In summary, these analysis results not only confirm that the hot-dip galvanized steel prepared by the present invention has the expected multilayer structure and phase composition, but also reveal its unique micromorphological characteristics, providing an important basis for a deep understanding of material properties.
[0071] Embodiment 2:
[0072] A method for preparing high-strength hot-dip galvanized steel comprises the following steps:
[0073] S1: Low carbon boron steel is reformed and formed into carbon steel parts; the composition of low carbon boron steel is C: 0.22%, B: 0.0016%; Si: 0.03%, P: ≦0.020%, Cr: 0.13%, and the rest is Fe.
[0074] S2: Use 5% by mass hydrochloric acid to pickle and remove rust on the surface of the carbon steel parts, then use 50% by mass acetone and water mixture to remove stains on the surface of the carbon steel parts, and then dry.
[0075] S3: The carbon steel parts cleaned in step S2 are subjected to step heating in sequence to achieve micro-decarburization on the surface of the carbon steel parts. After the step heating is completed, quenching treatment is immediately carried out. After the quenching is completed, the parts are tested. After the test is qualified, the quenched carbon steel parts are obtained. The process parameters of the step heating are: from room temperature to 342°C at a rate of 2°C / min, then to 552°C at a rate of 1.5°C / min, and then to the quenching temperature at a rate of 0.8°C / min. The quenching temperature is 759°C. The heating atmosphere for the step heating is a mixed atmosphere of nitrogen and methanol. The carbon potential of the heating atmosphere is 0.09%. The quenching liquid used during quenching is a polyalkylene glycol aqueous solution with a mass fraction of 2%, and the temperature of the quenching liquid is 37°C. The hardness of the quenched carbon steel parts is greater than 40HRC, and the thickness of the surface micro-decarburization layer is 0.045mm.
[0076] S4: The quenched carbon steel part obtained in step S3 is successively pickled and washed with water within 1 hour after being discharged, and a plating-assisting solution is used for plating-assisting treatment;
[0077] The pickling is carried out by using a pickling agent, and the pickling time is 5 minutes. The preparation method of the pickling agent comprises the following steps: adding ferrous chloride to hydrochloric acid with a mass fraction of 5.3%, stirring and mixing to obtain the pickling agent; the concentration of ferrous chloride in the pickling agent is 65g / L;
[0078] The plating-aiding solution is an aqueous solution containing 215 g / L ammonium chloride and 7 g / L zinc chloride. The pH value of the plating-aiding solution is adjusted to 4.3 with hydrochloric acid. The temperature of the plating-aiding treatment is 33° C. and the time is 48 s.
[0079] S5: Immerse the carbon steel parts obtained by step S4 in molten zinc liquid for hot-dip galvanizing, and then perform centrifugal dezincification, water cooling, and discharging treatment in sequence to obtain high-strength hot-dip galvanized steel. The composition of the molten zinc liquid is: Fe: 0.25%, Ni: 0.035%, Al: 0.018%, and the rest is Zn. The process parameters of hot-dip galvanizing are: hot-dip galvanizing temperature is 526℃, and hot-dip galvanizing time is 28s. The speed of centrifugal dezincification is 580rpm; the water cooling temperature is 66℃.
[0080] The high-strength hot-dip galvanized steel in this embodiment includes a carbon steel layer, a transition layer and a galvanized layer located on the carbon steel layer, wherein the transition layer is located between the carbon steel layer and the galvanized layer; the thickness of the galvanized layer is 52 μm; the thickness of the transition layer is 32 μm. The transition layer contains ζ-FeZn 13 ,δ-FeZn 10 and Fe2B; ζ-FeZn in the transition layer 13 The Fe2B columnar crystals in the transition layer have a serrated structure and are perpendicular to the transition layer interface. The average spacing of the Fe2B columnar crystals is 2.3 μm.13 and δ-FeZn 10 Evenly distributed between the Fe2B columnar crystals; the α-Fe in the carbon steel layer and the Fe2B phase in the transition layer form a lattice matching interface.
[0081] Embodiment 3:
[0082] A method for preparing high-strength hot-dip galvanized steel comprises the following steps:
[0083] S1: Low carbon boron steel is transformed and formed into carbon steel parts; the composition of low carbon boron steel is C: 0.24%, B: 0.0022%; Si: 0.04%, P: ≦0.020%, Cr: 0.16%, and the rest is Fe.
[0084] S2: Use 5% by mass hydrochloric acid to pickle and remove rust on the surface of the carbon steel parts, then use 50% by mass acetone and water mixture to remove stains on the surface of the carbon steel parts, and then dry.
[0085] S3: The carbon steel parts cleaned in step S2 are subjected to step heating in sequence to achieve micro-decarburization on the surface of the carbon steel parts. After the step heating is completed, quenching treatment is immediately carried out. After the quenching is completed, the parts are tested. After the test is qualified, the quenched carbon steel parts are obtained. The process parameters of the step heating are: from room temperature to 356°C at a rate of 3°C / min, then to 555°C at a rate of 2°C / min, and then to the quenching temperature at a rate of 1°C / min. The quenching temperature is 798°C. The heating atmosphere for the step heating is a mixed atmosphere of nitrogen and methanol. The carbon potential of the heating atmosphere is 0.10%. The quenching liquid used during quenching is a polyalkylene glycol aqueous solution with a mass fraction of 2%, and the temperature of the quenching liquid is 38°C. The hardness of the quenched carbon steel parts is greater than 40HRC, and the thickness of the surface micro-decarburization layer is 0.06mm.
[0086] S4: The quenched carbon steel parts obtained in S3 are successively pickled and washed with water within 1 hour after being discharged, and a plating-assisting solution is used for plating-assisting treatment;
[0087] The pickling is carried out by using a pickling agent, and the pickling time is 5 minutes; the preparation method of the pickling agent comprises the following steps: adding ferrous chloride to hydrochloric acid with a mass fraction of 5.6%, stirring and mixing to obtain the pickling agent; the concentration of ferrous chloride in the pickling agent is 80 g / L;
[0088] The auxiliary plating solution is an aqueous solution containing 230 g / L ammonium chloride and 8 g / L zinc chloride. The pH value of the auxiliary plating solution is adjusted to 4.6 with hydrochloric acid. The temperature of the auxiliary plating treatment is 36°C and the time is 66s.
[0089] S5: The carbon steel parts obtained by S4 treatment are immersed in molten zinc liquid for hot-dip galvanizing, and then centrifugal dezincification, water cooling, and discharging treatment are carried out in sequence to obtain high-strength hot-dip galvanized steel. The composition of the molten zinc liquid is: Fe: 0.29%, Ni: 0.039%, Al: 0.021%, and the rest is Zn. The process parameters of hot-dip galvanizing are: hot-dip galvanizing temperature is 532℃, and hot-dip galvanizing time is 31s. The speed of centrifugal dezincification is 610rpm; the water cooling temperature is 72℃.
[0090] The high-strength hot-dip galvanized steel of this embodiment includes a carbon steel layer, a transition layer and a galvanized layer located on the carbon steel layer. The transition layer is located between the carbon steel layer and the galvanized layer. The thickness of the galvanized layer is 64 μm. The thickness of the transition layer is 44 μm. The transition layer contains ζ-FeZn 13 ,δ-FeZn 10 and Fe2B; ζ-FeZn in the transition layer 13 The Fe2B columnar crystals in the transition layer have a serrated structure and are perpendicular to the transition layer interface. The average spacing of the Fe2BB columnar crystals is 3 μm. 13 and δ-FeZn 10 Evenly distributed between the Fe2B columnar crystals; the α-Fe in the carbon steel layer and the Fe2B phase in the transition layer form a lattice matching interface.
[0091] Embodiment 4:
[0092] A method for preparing high-strength hot-dip galvanized steel comprises the following steps:
[0093] S1: Low carbon boron steel is reformed and formed into carbon steel parts; the composition of low carbon boron steel is C: 0.27%, B: 0.003%; Si: 0.06%, P: ≦0.020%, Cr: 0.20%, and the rest is Fe.
[0094] S2: Use 5% by mass hydrochloric acid to pickle and remove rust on the surface of the carbon steel parts, then use 50% by mass acetone and water mixture to remove stains on the surface of the carbon steel parts, and then dry.
[0095] S3: The carbon steel parts cleaned in step S2 are subjected to step heating in sequence to achieve micro-decarburization on the surface of the carbon steel parts. After the step heating is completed, quenching treatment is immediately carried out. After the quenching is completed, the parts are tested. After the test is qualified, the quenched carbon steel parts are obtained. The process parameters of the step heating are: from room temperature to 350℃ at a rate of 5℃ / min, then to 560℃ at a rate of 3℃ / min, and then to the quenching temperature at a rate of 1.5℃ / min. The quenching temperature is 850℃. The heating atmosphere of the step heating is a mixed atmosphere of nitrogen and methanol. The carbon potential of the heating atmosphere is 0.12%. The quenching liquid used in quenching is a polyalkylene glycol aqueous solution with a mass fraction of 2%, and the temperature of the quenching liquid is 40℃. The hardness of the quenched carbon steel parts is greater than 40HRC, and the thickness of the surface micro-decarburization layer is 0.08mm.
[0096] S4: The quenched carbon steel part obtained in step S3 is successively pickled and washed with water within 1 hour after being discharged, and a plating-assisting solution is used for plating-assisting treatment;
[0097] The pickling is carried out by using a pickling agent, and the pickling time is 6 minutes; the preparation method of the pickling agent comprises the following steps: adding ferrous chloride to hydrochloric acid with a mass fraction of 6%, stirring and mixing to obtain the pickling agent; the concentration of ferrous chloride in the pickling agent is 100 g / L;
[0098] The auxiliary plating solution is an aqueous solution containing 250 g / L ammonium chloride and 10 g / L zinc chloride. The pH value of the auxiliary plating solution is adjusted to 5 with hydrochloric acid. The temperature of the auxiliary plating treatment is 30~40℃, and the time is 30~90s.
[0099] S5: Immerse the carbon steel parts obtained by step S4 in molten zinc liquid for hot-dip galvanizing, and then carry out centrifugal dezincification, water cooling, and discharging treatment in sequence to obtain high-strength hot-dip galvanized steel. The composition of the molten zinc liquid is: Fe: 0.35%, Ni: 0.045%, Al: 0.025%, and the rest is Zn. The process parameters of hot-dip galvanizing are: hot-dip galvanizing temperature is 540℃, and hot-dip galvanizing time is 35s. The speed of centrifugal dezincification is 650rpm; the water cooling temperature is 80℃.
[0100] The high-strength hot-dip galvanized steel in this embodiment includes a carbon steel layer, a transition layer and a galvanized layer located on the carbon steel layer, wherein the transition layer is located between the carbon steel layer and the galvanized layer; the thickness of the galvanized layer is 80 μm, and the thickness of the transition layer is 60 μm. The transition layer contains ζ-FeZn 13 ,δ-FeZn 10 and Fe2B; ζ-FeZn in the transition layer 13 The Fe2B columnar crystals in the transition layer have a serrated structure and are perpendicular to the transition layer interface. The average spacing of the Fe2B columnar crystals is 4 μm.13 and δ-FeZn 10 Evenly distributed between the Fe2B columnar crystals; the α-Fe in the carbon steel layer and the Fe2B phase in the transition layer form a lattice matching interface.
[0101] Comparative Example 1:
[0102] The method is basically the same as Example 1, except that the quenching temperature in the step temperature increase in step S3 is 900°C, and the other parameters remain unchanged. Therefore, a higher quenching temperature will accelerate the diffusion of carbon atoms and promote surface decarburization. The final carbon steel part has a hardness of 38HRC and a thickness of the decarburized layer of 0.1mm.
[0103] Comparative Example 2:
[0104] The method is basically the same as Example 1, except that the carbon potential of the heating atmosphere in the step-by-step heating in step S3 is 0.06%, and the other parameters remain unchanged. The lower carbon potential increases the carbon concentration gradient between the steel surface and the surrounding atmosphere, promotes the outward diffusion of carbon atoms, and promotes surface decarburization. The hardness of the final carbon steel part is 36HRC, and the thickness of the decarburized layer formed is 0.11mm.
[0105] Comparative Example 3:
[0106] It is basically the same as Example 1, except that the hot-dip galvanizing temperature in step S5 is 480° C. A lower temperature will reduce the diffusion reaction between Fe and Zn, thereby reducing the thickness of the transition layer, so the thickness of the transition layer in this embodiment is 15 μm.
[0107] Comparative Example 4:
[0108] It is basically the same as Example 1, except that the hot-dip galvanizing temperature in step S5 is 580° C. A higher temperature will accelerate the diffusion reaction between Fe and Zn, thereby increasing the thickness of the transition layer, so the thickness of the transition layer in this embodiment is 83 μm.
[0109] Performance Testing:
[0110] Appearance inspection: The appearance quality inspection of hot-dip galvanized steel follows GB / T13912-2002 "Hot-dip Galvanizing Standard", which mainly evaluates the surface characteristics of the coating. The inspection content includes surface smoothness, defect inspection (such as nodules, roughness, zinc thorns), coating integrity (no peeling, no leakage), impurity inspection (no residual flux slag), and zinc nodules and zinc ash inspection in specific areas. The inspection is carried out by visual, touch and light methods to ensure that the surface is smooth, without obvious defects, and completely covers the substrate. This inspection method can quickly evaluate the surface quality of the product, ensure its aesthetics and basic anti-corrosion performance, which is particularly important for parts that may affect use or corrosion resistance. Only samples that meet all requirements can be judged as qualified in appearance quality.
[0111] Interface bonding strength: The bonding strength test between the coating and the substrate adopts GB / T6396-2008 standard and uses UTM5305 universal mechanical properties testing machine. Cut the sample along the coating direction, pre-cut small squares on the coating surface, and then -3 s -1 The peel test was performed at a strain rate of 1.5 %. The bonding strength was calculated by recording the maximum peel force and dividing it by the pre-cut area to evaluate the bonding quality between the coating and the substrate.
[0112] Corrosion resistance: The corrosion resistance test of the coating is based on the ASTM G108-94 standard, using the double-cyclic potentiodynamic reactivation method (DL-EPR). Electrochemical tests were performed at a scan rate of 1.5 mV / s in a solution of 0.5 mol / L H2SO4 + 0.01 mol / L KSCN. By comparing the maximum current density ratio (Ir / Ia) between forward and reverse scans, i.e., the reactivation rate DOS (%), the corrosion resistance of the coating is evaluated, providing an important reference for the protective effect of the coating.
[0113] Tensile strength: The overall mechanical properties of hot-dip galvanized steel are evaluated by tensile testing. The samples are cut vertically into 75mm×4mm specimens and tested using a universal testing machine. At a tensile rate of 1mm / min, the stress-strain curve is recorded, and the deformation and peeling of the coating are observed. The mechanical properties of hot-dip galvanized steel are fully evaluated by measuring parameters such as tensile strength and elongation at break.
[0114] The properties of the hot-dip galvanized steels of Examples 1 to 4 and Comparative Examples 1 to 4 are summarized in Table 1.
[0115] Table 1 Performance summary of hot-dip galvanized steel in Examples 1 to 4 and Comparative Examples 1 to 4
[0116]
[0117] The main difference between Comparative Example 1 and Example 1 is the quenching temperature. As can be seen from Table 1, a higher quenching temperature (900°C) leads to a decrease in the interface bonding strength and tensile strength, while the reactivation rate DOS and elongation increase. This is because a higher quenching temperature accelerates the diffusion of carbon atoms, promotes surface decarburization, and forms a thicker decarburization layer (0.1 mm). The presence of the decarburization layer reduces the strength of the steel surface, thereby affecting the bonding strength between the coating and the substrate. At the same time, due to the decrease in surface strength, the overall tensile strength of the material also decreases, but the ductility increases. The thicker decarburization layer also leads to a decrease in surface corrosion resistance, so the reactivation rate DOS increases.
[0118] The main difference between Comparative Example 2 and Example 1 is the carbon potential of the heating atmosphere. As can be seen from Table 1, the lower carbon potential (0.06%) also leads to a decrease in the interface bonding strength and tensile strength, and an increase in the reactivation rate DOS and elongation. This is because the lower carbon potential increases the carbon concentration gradient between the steel surface and the surrounding atmosphere, promotes the outward diffusion of carbon atoms, and aggravates the surface decarburization (forming a 0.11 mm thick decarburization layer). This more significant decarburization effect is similar to Comparative Example 1, resulting in a decrease in surface strength, affecting the coating bonding strength and overall tensile properties. At the same time, the surface corrosion resistance decreases due to decarburization, resulting in an increase in the reactivation rate DOS.
[0119] The main difference between Comparative Example 3 and Example 1 is the lower hot-dip galvanizing temperature (480°C). As can be seen from Table 1, the lower galvanizing temperature leads to a slight decrease in the interface bonding strength, but a slight improvement in the reactivation rate DOS. The tensile strength and elongation do not change much. This is because the lower temperature reduces the diffusion reaction between Fe and Zn, forming a thinner transition layer (15μm). The thin transition layer slightly reduces the bonding strength between the coating and the substrate, but at the same time improves the uniformity of the surface, thereby slightly improving the corrosion resistance.
[0120] The main difference between Comparative Example 4 and Example 1 is the higher hot-dip galvanizing temperature (580°C). As can be seen from Table 1, the higher galvanizing temperature leads to an increase in the interface bonding strength, but the reactivation rate DOS increases slightly. The tensile strength decreases slightly, while the elongation increases slightly. This is because the higher temperature accelerates the diffusion reaction between Fe and Zn, forming a thicker transition layer (83μm). The thick transition layer enhances the bonding strength between the coating and the substrate, but at the same time leads to an increase in surface unevenness, thereby slightly reducing the corrosion resistance. The higher galvanizing temperature has a certain annealing effect on the substrate, resulting in a slight decrease in tensile strength and a slight increase in ductility.
[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing high-strength hot-dip galvanized steel, characterized in that: The following steps are involved: S1: cleaning carbon steel parts; the composition of the carbon steel parts is: C: 0.20-0.27%, B: 0.001-0.003%, Si: 0.02-0.06%, P: ≦0.020%, Cr: 0.10-0.20%, and the rest is Fe; S2: performing stepwise heating on the carbon steel part obtained in step S1 to slightly decarburize the surface of the carbon steel part, and then performing quenching treatment to obtain a quenched carbon steel part; S3: pickling and water washing the quenched carbon steel part obtained in step S2 in sequence, and performing a plating-assisting treatment using a plating-assisting solution; S4: immersing the carbon steel part obtained by the treatment in step S3 into a molten zinc solution for hot-dip galvanizing, and then sequentially performing centrifugal dezincification, water cooling, and discharging treatment to obtain the high-strength hot-dip galvanized steel; The high-strength hot-dip galvanized steel comprises a carbon steel layer, a transition layer and a galvanized layer located on the carbon steel layer, wherein the transition layer is located between the carbon steel layer and the galvanized layer, the thickness of the transition layer is 20-60 μm, and the thickness of the galvanized layer is 40-80 μm; The transition layer contains ζ-FeZn 13 ,δ-FeZn 10 and Fe2B; The transition layer contains ζ-FeZn 13 Form a lattice matching interface with Fe2B; The Fe2B columnar crystals in the transition layer present a tooth-like structure and are perpendicular to the transition layer interface; the average spacing of the Fe2B columnar crystals is 2-4 μm; The ζ-FeZn in the transition layer 13 and δ-FeZn 10 Evenly distributed between Fe2B columnar crystals.
2. The method for preparing high-strength hot-dip galvanized steel according to claim 1, characterized in that: In step S2, the process parameters of the step heating are: first, heating from room temperature to 340-350°C at a rate of 1-5°C / min, then heating to 550-560°C at a rate of 1-3°C / min, and then heating to the quenching temperature at a rate of 0.5-1.5°C / min. The quenching temperature is 720-850°C. The heating atmosphere for the step heating is a mixed atmosphere of nitrogen and methanol; the carbon potential of the heating atmosphere is 0.08-0.12%.
3. The method for preparing high-strength hot-dip galvanized steel according to claim 2, characterized in that: In the step S2, the quenching liquid used in the quenching is a 2% by mass polyethylene glycol aqueous solution, and the temperature of the quenching liquid is 35-40° C.; The hardness of the quenched carbon steel part is greater than 40HRC, and the thickness of the surface micro-decarburization layer is 0.03-0.08mm.
4. The method for preparing high-strength hot-dip galvanized steel according to claim 1, characterized in that: In the step S3, the quenched carbon steel part obtained in step S2 is sequentially subjected to pickling, water washing and plating treatment within 1 hour after discharge; The pickling is carried out by using a pickling agent, and the pickling time is 4 to 6 minutes; the preparation method of the pickling agent comprises the following steps: adding ferrous chloride to hydrochloric acid with a mass fraction of 5 to 6%, stirring and mixing to obtain the pickling agent; the concentration of ferrous chloride in the pickling agent is 50 to 100 g / L; The plating-assisting solution is an aqueous solution containing 200-250 g / L ammonium chloride and 5-10 g / L zinc chloride, and the pH value of the plating-assisting solution is adjusted to 4-5 with hydrochloric acid; The temperature of the plating assist treatment is 30-40° C. and the time is 30-90 seconds.
5. The method for preparing high-strength hot-dip galvanized steel according to claim 1, characterized in that: In step S4, the composition of the molten zinc solution is: Fe: 0.2-0.35%, Ni: 0.030-0.045%, Al: 0.015-0.025%, and the rest is Zn; The temperature of the hot-dip galvanizing is 520-540° C., and the time is 25-35 seconds.
6. The method for preparing high-strength hot-dip galvanized steel according to claim 1, characterized in that: The α-Fe in the carbon steel layer and the Fe2B phase in the transition layer form a lattice matching interface.
7. Application of high-strength hot-dip galvanized steel prepared by the preparation method as described in any one of claims 1 to 6 in grade 8 to grade 10 nut hot-dip galvanized layer fasteners.
